2006
DOI: 10.1007/s10484-006-9005-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biofeedback in Phonatory Disorders and Phonatory Performance: A Systematic Literature Review

Abstract: The purpose of this article was to systematically review the literature on the effects of biofeedback therapy in the domain of phonatory disorders and phonatory performance, using studies in peer-reviewed journals. An extensive definition of biofeedback is given and its place in voice treatment is defined. Eighteen group or case studies or reports considering the effects of electromyographic, laryngoscopic and acoustic biofeedback in dysphonic patients (hyperfunctional voice disorders, hypofunctional voice dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 60 publications
1
12
0
3
Order By: Relevance
“…Die Intervention bezog sich auf diverse konventionelle Therapieverfahren und jeder Patient erhielt eine individuelle Mischung aus den folgenden Methoden, wie z. B. Larynxmanipulation [28], Semi-Occluded Vocal Tract Übungen [29,30], Biofeedback [31] und lokale Vibrationstherapie [32].…”
Section: Resultsunclassified
“…Die Intervention bezog sich auf diverse konventionelle Therapieverfahren und jeder Patient erhielt eine individuelle Mischung aus den folgenden Methoden, wie z. B. Larynxmanipulation [28], Semi-Occluded Vocal Tract Übungen [29,30], Biofeedback [31] und lokale Vibrationstherapie [32].…”
Section: Resultsunclassified
“…A total of 51 studies were identified (Figure 1), of which, 16 (16)(17)(18)(19)(20)(23)(24)(25)(28)(29)(30)(31)(32)(33)(34)(35) were relevant to the topic. When the complete articles were read and the selection criteria for this study were applied, the study's design excluded 11 articles (16,17,19,24,(29)(30)(31)(32)(33)(34)(35) .…”
Section: Discussionmentioning
confidence: 99%
“…Biofeedback is the equipment to assist the patients to control voluntarily the strength of muscular contraction that is joined the vocal cord adduction process. However, the increase of adductor muscular contraction strength in KAKVI after the BF voice therapy is still unclear [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%